Decision Prioritization with MCDM in Post-Disaster Management: A PRISMA-Guided Systematic Review and Bibliometric Mapping - Agusta Praba Ristadi Pinem; Rahmat Gernowo; Sorja Koesuma (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2026)
Prioritizing post-disaster actions requires balancing multiple, often conflicting criteria. To consolidate scattered evidence, this study reviews decision prioritization with Multi-Criteria Decision-Making (MCDM) in post-disaster management using a PRISMA-guided systematic review and bibliometric mapping. Initial searches returned 18,454 records from Scopus, 47,206 from Google Scholar, 650 from Emerald Insight, 30,975 from ProQuest, and 4,468 from IEEE Xplore. We included English-language articles published between 2014 and 2025—a window chosen to capture the rise of hybrid and fuzzy variants and early integrations with GIS, AI, and big data—that apply MCDM to prioritizing projects, interventions, or sites. We excluded non-English items, duplicates, and incomplete records; screening and eligibility followed PRISMA. We combined SLR procedures with bibliometric analysis in VOSviewer and R-bibliometrix to map co-occurrence. From the pool, 32 studies met the criteria. Distance-based methods (TOPSIS, VIKOR, EDAS) and AHP dominate; hybrid and fuzzy variants are increasing. Objective and mixed weighting are common, while normalization choices and ranking rules vary by context. Validation is uneven: case applications and expert judgment are common, but sensitivity tests and cross-method comparisons are scarce. We connect objectives, weighting and normalization, ranking, and validation, identify method–context fit, and spotlight reporting gaps. We provide method-selection cues and a reporting checklist for practitioners, and a roadmap for standardized validation, transparent parameterization, and integration with GIS, AI, and big data for researchers.